Preliminary FEA Simulation of Piezoelectric Generator for Pipeline Monitoring Sensor - Jaifani, A.S.R. (Institute of Electrical and Electronics Engineers Inc., 2021)
This research proposes the development of an energy harvesting device that generates electrical power to be applied specifically for the pipeline monitoring system. Issues with the limited power supply of the pipeline monitoring system will be resolved by the conversion of vibration or mechanical energy into electrical energy, allowing real-time monitoring that can intelligently monitor the integrity of the underground pipelines continuously. For the preliminary Finite Element Analysis (FEA) simulation, a model was designed using the COMSOL software and was then studied. Some of the critical studies for the FEA is to find out the trend of frequency response, load dependence and acceleration dependence from a model towards its effect on the output voltage and power. The simulation shows that the piezoelectric generator modelled was able to provide its peak voltage and output when operating at its optimal condition at vibrating acceleration of 1 g. From the studies, significant trends can be recorded and analysed to enhance further future designs that apply piezoelectricity to convert electrical energy from sources of kinetic energy. Â© 2021 IEEE.